2006
DOI: 10.1290/0512089.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Estrogen Receptors and Relaxin Binding in Human Anterior Cruciate Ligament Fibroblasts

Abstract: The significantly higher incidence of anterior cruciate ligament (ACL) injuries in collegiate women compared with men may result from relative ligament laxity. Differences in estrogen and relaxin activity, similar to that seen in pregnancy, may account for this. We quantified estrogen receptors by flow cytometry and relaxin receptors by radioligand binding assay in human ACL cells and compared the presence of these receptors in males and females. ACL stumps were harvested from seven males and eight females wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 33 publications
1
38
0
1
Order By: Relevance
“…Fibroblasts from human ACL, medial cruciate ligament and patellar tendon express functional ER transcripts. Indeed, 4 to 10% of ACL cells express ERs in patients with acute ACL injuries, approximately twice the proportion found in control subjects [13,71]. In human skeletal muscle, ERα mRNA expression was 180-fold higher than that of ERβ [72].…”
Section: Mechanisms Underlying the Effects Of Estrogen On Joint Tissuesmentioning
confidence: 99%
“…Fibroblasts from human ACL, medial cruciate ligament and patellar tendon express functional ER transcripts. Indeed, 4 to 10% of ACL cells express ERs in patients with acute ACL injuries, approximately twice the proportion found in control subjects [13,71]. In human skeletal muscle, ERα mRNA expression was 180-fold higher than that of ERβ [72].…”
Section: Mechanisms Underlying the Effects Of Estrogen On Joint Tissuesmentioning
confidence: 99%
“…Both relaxin receptors and their transcripts have been identified in reproductive and non-reproductive tissues such as the brain, kidney, lung, anterior cruciate ligament of the knee joint and in synovial joint fibrocartilaginous cells (Faryniarz et al, 2006; Hsu et al, 2002; Wang et al, 2009). Although the precise contributions of RXFP1 and RXFP2 to modulation of MMPs upon activation by relaxin are not known, indirect evidence for the role of RXFP1 to in vivo remodeling of matrices is provided by the phenotypic characteristics of the female RXFP1 null mice that are similar to those described for relaxin-deficient mice (Kamat et al, 2004; Krajnc-Franken et al, 2004; Zhao et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Several histologic studies have shown that relaxin binds with specificity to tissue samples of the anterior cruciate ligament. [7][8][9] Initially considered a potential risk factor for female athletic injuries, currently no evidence has accrued to suggest that high serum levels of relaxin contribute to anterior cruciate ligament injury. 10 While anecdotal observations have noted increased joint laxity associated with pregnancy, 11 it remains unclear whether joint hypermobility, as a singular or cumulative event, causes injury or pathology.…”
Section: Introductionmentioning
confidence: 99%